Obstacle Recognition Method of Anti-collision System of Mine Locomotive - GUO Jiang-tao (Gong-kuang zidonghua, 2012)
The paper analyzed characteristics of images of obstacle in front of running locomotive obtained by camera of anti-collision system of mine locomotive, and proposed recognition methods of obstacle away from the locomotive with short, middle and long distances and their realization flows. The testing result showed the method can obtain characteristics of obstacles validly and recognize the obstacles quickly.